Spatial variations in soil properties across ecotones: a short review - Marfo, Theodore Danso; Resjek, Klement; Vranova, Valerie (Bulletin of Geography. Physical Geography Series, 2018)
Ecotones are considered as unique environments. The concepts of edge effect and ecotone species (flora and fauna) are widely used. Considering the fact that, majority of the species found at ecotones are usually at their physiologically determined limits of distribution, how ecotones react to global climate changes become crucial. Ecotones can also be likened to semi-permeable membranes of cells as happenings inside ecotones can influence concentrations of dissolved and suspended substances found in ecotones or the fluxes that move into and out of ecotones. Ecotones are reputed to be more biologically diverse than areas close to it therefore possesses a high conservation value yet little is known on how soil properties vary across ectones. In this paper, we firstly highlighted the roles ecotones play in assessing the effect on global climate change, the mediatory role it plays in material (water and nutrients) movement into and out of the region. Secondly, we reviewed researches on how soil properties change across ecotones and it is worthwhile to note that, soil properties tend to differ across various ecotones (e.g. increasing pH and decreasing P & N across forest-glade ecotones, decreasing pH across ancient- recent forest ecotones) in a manner that defines the character of the ecotones existing